2014
DOI: 10.1007/s10681-014-1163-8
|View full text |Cite
|
Sign up to set email alerts
|

Using tube rhizotrons to measure variation in depth penetration rate among modern North-European winter wheat (Triticum aestivum L.) cultivars

Abstract: Deeper plant root systems are desired for improved water and nitrogen uptake in leaching environments. However, phenotyping for deep roots requires methods that enable plants to develop deep roots under realistic conditions. Winter cereals raise further complications as early growth occurs under low light and temperature during autumn and winterconditions not met in standard glasshouse facilities. This study used tube rhizotrons of 2 m length, positioned outdoor under a rainout shelter to screen for depth pene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…The hydroponic technique used in this study showed that the QCCPs had larger root and shoot systems. Greater seedling vigour in root and shoot growth affects N uptake in wheat , and rooting depth of winter wheat genotypes is important for the uptake of nitrogen during stem elongation and grain filling (Ytting et al, 2014). Under limited supply of available nitrogen in early developmental phases, as common in organic farming, early shoot growth will result in higher photosynthesis, resulting in more assimilates being translocated to the roots Kamiji et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The hydroponic technique used in this study showed that the QCCPs had larger root and shoot systems. Greater seedling vigour in root and shoot growth affects N uptake in wheat , and rooting depth of winter wheat genotypes is important for the uptake of nitrogen during stem elongation and grain filling (Ytting et al, 2014). Under limited supply of available nitrogen in early developmental phases, as common in organic farming, early shoot growth will result in higher photosynthesis, resulting in more assimilates being translocated to the roots Kamiji et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Prospects for genetic improvements to the root penetration rate of wheat are under investigation and have been discussed in recent papers (Palta et al, 2011;Wasson et al, 2012), and some evidence for varietal differences has been suggested (Wasson et al, 2012(Wasson et al, , 2014Ytting et al, 2014;Rasmussen et al, 2015), though these are yet to be adequately separated from influences of flowering time and length of vegetative stage. A study from Western Australia showed a significant interaction between soil conditions and genotypes for deep rooting, indicating that it may be difficult to breed genotypes with a general ability to form deeper root systems (Acuna and Wade, 2012).…”
Section: Factors Influencing Deep Root Growthmentioning
confidence: 99%
“…(Forde and Lorenzo 2001;White et al 2013). Root development was analysed in plants grown in the field *Corresponding author; E-mail: juanm.gonzalez@uah.es 70 González et al: Root System Architecture in Brachypodium Cereal Research Communications 44, 2016 (Trachsel et al 2011), in pots filled with sand or soil (Waines and Ehdaie 2007) and in rhizotrons (Tyagi et al 2014;Ytting et al 2014). In all these studies, however, the roots had to be extracted and washed before any phenotypic examination could be made.…”
Section: Introductionmentioning
confidence: 99%